2021
DOI: 10.31584/jhsmr.2021797
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Severity and Relationship of Anaemia with Immune Status and Use of Highly Active Antiretroviral Therapy among Human Immunodeficiency Virus-Infected Adults in South-eastern Nigeria

Abstract: Objective: Anaemia is a significant complication of human immunodeficiency infection, causing life-threatening symptoms and impairing quality of life. This study aimed to assess the prevalence, severity and associations of anaemia, with cluster of differentiation 4 (CD4+) cell count and use of highly active antiretroviral therapy (HAART), in human immunodeficiency virus-infected patients. Material and Methods: Haemoglobin concentration, CD4+ count, HAART use and other factors were assessed in 372, adult HIV-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
1
1
2
Order By: Relevance
“…Our finding is lower than the results of several studies [ 13 , 14 , 28 , 29 ]. Studies conducted in Calabar, Nigeria (76.0%) [ 14 ], Southeastern Nigeria (76.3%) [ 13 ], Uganda (47.8%) [ 28 ], and China (51.9%) [ 29 ] reported higher prevalence than ours.…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…Our finding is lower than the results of several studies [ 13 , 14 , 28 , 29 ]. Studies conducted in Calabar, Nigeria (76.0%) [ 14 ], Southeastern Nigeria (76.3%) [ 13 ], Uganda (47.8%) [ 28 ], and China (51.9%) [ 29 ] reported higher prevalence than ours.…”
Section: Discussioncontrasting
confidence: 98%
“…Our finding is lower than the results of several studies [ 13 , 14 , 28 , 29 ]. Studies conducted in Calabar, Nigeria (76.0%) [ 14 ], Southeastern Nigeria (76.3%) [ 13 ], Uganda (47.8%) [ 28 ], and China (51.9%) [ 29 ] reported higher prevalence than ours. The inclusion of many female participants in those studies done in Nigeria could be one possible reason for the disparity.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…This study showed a significant association (p=0.001) between sex and the risk of anemia in HIV patients. This is in line with the result that women living with HIV/AIDS are more prone to anemia than men (Nnamani et al, 2021). A significant correlation (p=0.002) was also discovered between age and the incidence of anemia in patients administered AZT.…”
Section: Resultssupporting
confidence: 88%